0904 Rapid Eye Movement Related Obstructive Sleep Apnea In The Pediatric Population: Case Series And Considerations. (27th May 2020) - Petitto, L; Musso, M
Abstract: Introduction: Rapid Eye Movement (REM) related Obstructive Sleep Apnea (OSA) can impact sleep quality and result in negative clinical consequences. There are limited pediatric studies evaluating potential consequences, looking at optimal decision making, and discussing best treatment options. Aims: 1: Describe clinical impact and potential negative consequences; 2: Discuss treatment management of REM related OSA; 3: Evaluate clinical effectiveness of treatment. Methods: Case series: Retrospective review of 22 pediatric patients with REM related OSA at a tertiary care center. Clinical analysis of implemented treatment modality vs. observation was reviewed. Symptomatic response to treatment modality vs. observation including alteration of quality of life was examined. Results: REM related OSA lead to negative clinical daytime symptoms which warranted consideration and implementation of further treatment. Conclusion: Treatment considerations for REM related OSA include tonsillectomy and adenoidectomy, positive airway pressure, medical management, and watchful waiting. Further research is necessary to increase knowledge of clinical impact of REM related OSA and treatment. Support: N/A